Bahasa Ciacia Dan Aksara Kontemporernya - Laksono, M. Hum., Prof. Dr. Kisyani (LPPM Universitas PGRI Adi Buana Surabaya, 2015)
Ciacia language is a regional in Indonesia, which has used Korean Hangul Alphabet.